ESP IDF programming for IoT: a blueprint for facial recognition in attendance systems in IIUM - Zainuddin, Ahmad Anwar; Mustapa, Nurul Salshabila; Mohd Nor, Rizal; Amir Hussin, Amir 'Aatieff; Nik Mohd Kamal, Nik Nor Muhammad Saifudin; Md Saifuddin, Muhammad Hafiz Faruqi; Abdul Halim, Ahmad Adlan; Ahmad Faizul, Nur Adila; Ruzaidi, Nuramiratul Aisyah; Mohd Razali, Muhammad Irfan Zaki; Fazail, Muhammad Nazmi (Universiti Kuala Lumpur Publishing, 2024)
An attendance system based on facial recognition that uses several microcontrollers and microprocessors is studied in this work. The present study introduces the proposed model and afterward discusses the results obtained from different tests conducted utilising a range of microcontrollers. The ESP32-S3 microcontroller is programmed via the Espressif IoT Development Framework (ESP IDF) in order to generate full instructions for the Internet of Things (IoT) device. The incorporation of specific components, such as Pseudostatic Random Access Memory (PSRAM), a camera interface peripheral, and USB peripherals, facilitates efficient connectivity with a camera. The present study highlights the constraints associated with the utilisation of Raspberry Pi 3B, encompassing the issue of device sluggishness and the requirement for USB cameras with lower resolutions to expedite processing. This paper offers valuable insights into the examination and implementation of contemporary advancements and investigations in the field of face and object recognition system development. From this study, approximately 126 students actively participated in the demonstration. The analysis of the results indicates a noteworthy 70% accuracy rate among the participants.